ZAIDMAN, Louise Bruit; SCHMITT-PANTEL, Pauline. La religion grecque. Paris: Armand Colin, 1991. 190p - Brandão, Jacyntho Lins (Classica - Revista Brasileira de Estudos Clássicos, 1993)
ZAIDMAN, Louise Bruit; SCHMITT-PANTEL, Pauline. La religion grecque. Paris: Armand Colin, 1991. 190p